(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
Machiavellian leadership, an emerging form of toxic leadership, has been noticed to have serious negative effects on organizations. Thus, expanding the literature on dark styles of leadership, this study specifically examines the mechanism via which Machiavellian leadership of departmental heads (HODs) may hinder university teachers’ creativity by considering the mediating effect of teachers’ enterprising tendency. Furthermore, the study considers leader-member exchange (LMX) as a moderator that buffers the dysfunctional effects of Machiavellian leadership. A dual-source data was collected from 303 teachers and 32 HODs of two leading universities in Islamabad. Findings from statistical analyses confirm that the Machiavellian leadership–creativity relationship is mediated by teachers enterprising tendency. Also, the Machiavellian leadership and enterprising tendency relationship is moderated by LMX, such that the relationship is more evident under higher levels of LMX. In total, this study’s findings expand the understanding regarding why, when and how Machiavellian leadership may hinder employees’ creativity.